A Systematic Review of Youth-to-Parent Aggression: Conceptualization, Typologies, and Instruments - Ibabe, Izaskun (Frontiers in Psychology, 2020)
The goal of this study was to analyze the conceptualization of YPA (youth-to-parent aggression) in relation to terms, definitions, typologies and assessment instruments. To achieve this aim, a systematic review was carried out using the PRISMA protocol. Assessment instruments for YPA were examined in accordance with COSMIN (Consensus-based Standards for the Selection of Health Measurement Instruments). After reviewing the literature on conceptualization and measuring instruments, some gaps were found. The use of some particular terms was justified depending on the age of children and severity of case. Taking into account the theoretical background, a full definition of YPA was offered. Moreover, this study revealed that it was possible to discriminate four typologies of YPA (Offensive, Defensive, Affective, and Situational) as a function of the coercion level and nature of the violence. Eleven instruments to measure YPA were analyzed exhaustively, with the most reported and robust psychometric properties being internal consistency and structural validity, while other validity evidence was understudied. The CPV-Q (12–25 years) obtained the highest rating as a promising instrument. The initial psychodiagnosis of a YPA situation would help in the individual or family intervention, as well as prevent more severe situations of YPA through early intervention.